CHRISTOPHER COLUMBUS AND THE GENESIS OF NEW WORLD COLONIALISM, 1493-96 - Rocca, Al M. Link ([S.l.])
1 online resource
Keywords: This book explores the role of geography's five themes: location, place, human-environmental interaction, movement, and region, in Christopher Colombus's second voyage. It explores the impacting events that led to deteriorating relations between Columbus, the Spanish settlers (adventurers), and the indigenous Tano and Carib people, creating a social paradigm of confusion, displacement, destruction, and the genesis of New World Colonization.